Enhancing Students’ Responsibility Through Qur’an Memorization Activities at TPQ Thoyyibah - Hilda Brilliant Bilqis; Triono Ali Mustofa (FKIP - Universitas Riau, 2026)
This research looks at how TPQ Thoyyibah Banyuanyar's Qur'an memorization deposit program is used to help pupils become more responsible In Islamic educational environments, responsibility is seen as a crucial character characteristic that must be cultivated by consistent practice, habituation, and discipline. Ten students chosen via purposive sampling based on their active engagement in memorizing exercises, two instructors, and one TPQ head participated in this descriptive qualitative research Observations, interviews, and documentation were used to gather data. The results show that by encouraging regular preparation, timeliness, discipline, and consistency in memory assignments, the memorization deposit activity helps children improve their sense of responsibility. Throughout the learning process, students increasingly grew more conscious of their responsibilities. Additionally, instructors were crucial in directing, inspiring, and fostering a positive learning environment that inspired pupils to actively engage in memorizing exercises. Despite a number of issues, including varying motivation and disparities in memorizing skills, the program typically showed beneficial effects on kids' character development. Therefore, via repeated learning experiences and religious habituation, the memorization deposit program may be regarded as an excellent technique for enhancing students' character and feeling of duty in non-formal Islamic educational institutions.